Hepatitis-associated-antigen-positive hepatitis in a tuberculosis unit. Issue 6 (June 1975) - Fitzgerald, G R; Grimes, H; Reynolds, M; Hitchcock, H; McCarthy, C F
Abstract : An outbreak of hepatitis-associated-antigen-(HB Ag)-positive hepatitis in a hospital unit for the care of male patients with pulmonary tuberculosis is described. Sixty-four patients were studied of whom 37 were HB Ag positive. Hepatitis developed in at least 20 and was icteric in 11. The illness was mild, without fatality due to hepatitis and persistent jaundice did not occur. A carrier state developed in 15 of 24 HB Ag-positive patients followed up for more than six months and was unrelated to the presence or absence of initial hepatitis. Spread of HB Ag to domestic and medical staff occurred and following the discharge of the patients, household contacts became positive. Five, all wives of patients, developed jaundice. Faeces and sputum were HB Ag negative in seropositive cases. The origin of the outbreak remains undetected. The probability of non-parenteral transmission of HB Ag in this outbreak is discussed. Closure of the unit, isolation of HB Ag-positive cases with separate toilet and kitchen facilities, and discharge of patients when their respiratory condition allowed, resulted in prevention of further spread and eventually all patients were discharged from the unit.